Validation of FECPAKG2 equipment and prevalence of equine gastrointestinal parasites in Polo horses in Plateau State, Nigeria - J. G Golshang; N Nanvyat; E. R Edeh; M. N Patrobas; D. O Oshadu; C. H Dishion; A. A Dzikwi-Emennaa; E. O Otakpa; G. N Imandeh; L. H Lombin (BMC, 2024)
Abstract Gastrointestinal (GI) parasites are a global concern and cause serious damage to the health of animals, including horses, because of their deleterious effects on the health of these animals. Owing to improperly diagnosing the parasitic load and the resulting incorrect treatment, anthelmintics are becoming a global problem. Although rapid diagnostic techniques such as McMaster and FECPAKG2 are available in Africa, concentration techniques, including flotation and sedimentation, are commonly used in screening for gastrointestinal parasites. In this study, we compared the sensitivity of diagnostic techniques, namely, McMaster and FECPAKG2, in quantifying and determining the prevalence of gastrointestinal parasites as an alternative to the commonly used flotation and sedimentation techniques for equine fecal samples in Jos, Plateau State, Nigeria. Three hundred fecal samples were collected from different locations. The instructions provided by the manufacturers of FECPAKG2 and McMasters were used as the methodology for egg count per gram of fecal matter, while parasite egg/ova identification was performed through sedimentation and flotation techniques. In general, a prevalence of 66.3% was recorded, with a higher prevalence on Babale ranch (84%) than on Jos Polo Club (62%) and Jos mounted troop (53%). A total of nine gastrointestinal parasites were identified via both sedimentation and flotation techniques: Strongylus spp. (19.3%) was the most prevalent parasite identified via the flotation method, whereas Gastrodiscus aegyptiacus (25.3%) was the most prevalent parasite identified via the sedimentation technique. In general, FECPAKG2 had a sensitivity of 86%, whereas McMaster had a sensitivity of 64% in terms of egg counts per gram of fecal sample. This finding suggests that equines in Jos are highly infected with a variety of gastrointestinal parasites to varying degrees, with Strongylus spp. and Gastrodiscus aegyptiacus being more prevalent. Although the parasite load was found to range from low to moderate levels, the majority of the equine samples contained < 200 eggs per gram, suggesting a low infection rate via both the McMaster technique and the FECPAKG2 technique. On the basis of these findings, FECPAKG2 is recommended for rapid diagnosis because of its prompt outcome and infestation rate as well as ease of routine examination. Additionally, routine examination should be carried out to determine infestation by gastrointestinal parasites in all equine holdings and the effectiveness of the therapeutic agents used.